(untitled) (Global Journal of Human-Social Science, 2016)
African religion is a collection of the belief systems of Africans. It is one of the oldest religions of the world practiced in both rural and urban centres in Africa. The religion is known to possess many myths which play profound roles and strongly influence the understanding of the African environment, history, geography, religious ideas, medicine, and their social organisations. This paper unearths some African myths that have led to climate change and environmental degradation. The research employed extensive library study in collecting data on African myths, especially of West African peoples, which relate to climate. The paper relied on the anthropological and comparative methods of data analysis. The article is organised into segments. The first section is the introduction while the second locates the concepts of climate change and environmental degradation. The third segment identified African myths that promote climate change and environmental degradation along with their effects on the development of Africa. The research found that, African religion, besides its principal function of helping humans to live in harmony with God, the deities and with nature, possesses a certain measure of mythological dispositions leading to practices that result in bush burning/smoke emissions, earthquakes/landslides, desertification, drought, excessive rainfall and flooding, greenhouse effect, and locust invasion among other things.